(untitled) (Zaporizhzhia Historical Review, 2021)
The objective of this article is the activity of organizations (prikazs) of social guardianship as credit establishments. Bank operations appeared in the organizations (prikazs) only as auxiliary source of profit and in accordance with it they were regulated. Before offices of Commercial Bank were organized organizations (prikazs) were the only credit establishments, which were settled down in province. These establishments influenced on the development of marketing in the Herson province.